Study on the management program of Massai Mara national reserve based on indicator analysis - Wang, Junjie; Yu, Yu; Wang, Xuechun (Transactions on Computer Science and Intelligent Systems Research, 2024)
The Maasai Mara National Reserve is rated as one of the seven natural wonders of Africa and one of the ten wonders of the world. To reduce the impact of human activities on wildlife and further consolidate the balance between humans and nature, this paper proposes a research analysis method for the Massai Mara National Reserve. First, the influencing factors were divided into four indicators: wildlife, economy, resident life and non-animal resources. For these four indicators, eight main factors are further divided, including employment, native resource destruction, poaching, injuries to personnel, crop destruction, causing dissatisfaction among tourists, revenue brought in by tourists, the cost of conserving biological resources. The relationship between these factors and indicators produced the influence on the number of visitors and the development trend of human footprint. Subsequently, the reasons for these important indicators are analyzed, and corresponding solutions are put forward, such as strengthening the management of protected areas, expanding the scope of protected areas, and formulating unified charging standards.